Brain Activity to Study Physical Pain: A Survey of Tools and Methods - Chàvez-Sáenz, Velia; Torres, Vianey; Garay-Jiménez, Laura Ivoone; Tovar, Blanca (2021)
Pain is a problem that has a significant effect on the quality of life, both personal and social, and in the knowledge of the authors. To date, there is no practical device or method that allows us to generate a quantitative pain index. In recent years, studies related to pain and its measurement have been reported, which have used brain activity as a biological marker of pain based on various methodologies. Therefore, the purpose of this survey article is to concentrate the tools and methods that use brain activity to study two types of physical pain: 1) chronic, as a result of a clinical condition; and, 2) acute physical induced by a painful stimulus. The survey analyzes the elements involved in evaluating these types of pain, considering the number of subjects, the EEG setting, the stimulus applied, the pain perception test used, the software for analysis and processing, and additional resources. The results present a systematic classification of the information; it contains the techniques and technologies that have been used for the study of pain. Finally, the article concludes identifying opportunity areas as quantitative pain measurement tools based on brain activity analysis to understand, adapt, or monitor the treatment responses.